2023
DOI: 10.1002/clc.23971
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of low‐dose sacubitril/valsartan in heart failure patients: A systematic review and meta‐analysis

Abstract: Background: Controversy has persisted over the clinical benefits of low-dose sacubitril/valsartan in patients with heart failure (HF).Hypothesis: Low-dose sacubitril/valsartan might also be effective and safe in HF patients.Methods: Electronic databases including PubMed, Ovid, and Cochrane Library were systematically retrieved from inception to August 5, 2021. Review manager 5.4 and Stata 15.1 were employed in this systematic review and meta-analysis. Key efficacy outcomes of interest included HF hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…In assisted reproductive technology (ART), GH is used as an adjunct to ovarian stimulation in patients with a poor ovarian response (POR), although its role is still controversial. Several studies have reported that GH improves ART outcomes in POR patients (11,12), consistent with our recent reports that GH supplementation increases the clinical pregnancy and live birth rates (13,14). In animal models, GH supplementation has recently been show to improve the oocyte quality by enhancing mitochondrial function (15,16).…”
Section: Introductionsupporting
confidence: 80%
“…In assisted reproductive technology (ART), GH is used as an adjunct to ovarian stimulation in patients with a poor ovarian response (POR), although its role is still controversial. Several studies have reported that GH improves ART outcomes in POR patients (11,12), consistent with our recent reports that GH supplementation increases the clinical pregnancy and live birth rates (13,14). In animal models, GH supplementation has recently been show to improve the oocyte quality by enhancing mitochondrial function (15,16).…”
Section: Introductionsupporting
confidence: 80%